EVALUATION OF ANCHORAGE TECHNIQUE ON THE ADAPTION OF PARTIAL DENTURE FRAMEWORK (COMPARATIVE IN VITRO STUDY) - M Lefsaay, Amel; H Elgtlawi, Mohamed; E Burawi, Gamal (Libyan Journal of Dentistry, 2017)
The cast partial removable partial denture must be well fitted on the master dental cast and also on the oral tissues to be more successful and fulfill its functions. The objective of this in-vitro study was to evaluate the effect of anchorage on the accuracy of fit in removable partial denture framework. The study consisted of fourteen maxillary partially edentulous refractory casts Class III Kennedy classification modification 1 which were divided equally into two groups group I test group (Anchorage technique) and group II control group (Conventional technique). Seven cobalt chrome removable partial denture frameworks were constructed for each group, one using conventional technique with performed wax pattern on a refractory casts and other seven cobalt chrome removable partial denture frameworks were constructed using anchorage technique including four holes for anchorage on the refractory casts. Both patterns were invested and casted under the same circumstances using conventional standardized technique. The resulting metallic removable partial denture frameworks were evaluated to check the fitness of palatal strap the major connector on the master metal cast using digital micrometer. The statistical results of this study showed significant reduction in the thickness (gap) between the palatal strap major connector and its related site among group I (Anchorage) when compared with group II (Conventional) which indicating more accurate fit for group I. Furthermore, all the frameworks which were constructed by anchorage technique revealed more gap reduction centrally and anteriorly than peripherally and posteriorly.